Reinterpretasi Ketetapan Hukum Asuransi Perspektif Hukum Islam - Jamaluddin, Jamaluddin; Zahid, Reza Ahmad (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This article explores the legal aspects of the insurance industry with a focus on the perspective of Islamic law. In exploring this topic, the author identifies key concepts in Islamic law that are relevant to aspects of insurance law, such as the principles of sharia, fairness, and justice in risk sharing. The study includes an examination of the Islamic legal doctrines underlying conventional insurance regulations. The author also compares the principles of conventional insurance law and the principles of sharia, looking for common ground and discrepancies between the two. Through critical analysis of the views of Islamic scholars and Islamic legal literature, this article aims to provide a reinterpretation of insurance legal provisions, seeking alternatives that can accommodate the principles of Islamic law without compromising the sustainability and viability of the insurance industry. The findings of this research are expected to contribute to further understanding of how legal provisions in insurance can be harmonized with the principles of Islamic law. As a result, this article not only creates room for further discussion in the legal literature, but can also provide a foundation for further improvement or development regarding insurance regulation that integrates Islamic values.